Recent Progress in Medicinal Plants, Volume 13 : Search for Natural Drugs
Traditional Knowledge and Indigenous Uses of Tribal Medicinal Resources in India - A Review (INDIA), Ecballium elaterium (L.) A. Rich.: In vitro Regeneration and the Production of Cucurbitacins in Culture (MALTA), Effect of Oral Administration of Aloe barbadensis Miller Juice on Selected Biochemical Parameters of Rat Liver and Kidney (NIGERIA), Psidium sartorianum (O. Berg) Nied., An Indigenous Plant to Mexico, from Biology to Biological Activity (MEXICO), Antileishmanial Natural Products (INDIA), Antioxidant Properties and Photoactivity of Hydroxyanthraquinone (Aloe vera-derivate) (VENEZUELA), Antioxidant Properties and Health Benefits of Tomato (ITALY), Correlation Between Phenolic Content and In vitro Antioxidant Activities of Orthosiphon stamineus Leaf Extracts Using Principal Component Analysis (MALAYSIA), Traditional Knowledge and Indigenous Uses: Ethnobotanical Leads to Drug Discovery (AUSTRALIA), Acetylcholinesterase Inhibitory Activity in Extracts and Compounds from Flowering Plants (UK), Pharmacognostical Standardization of Galls of Mayaphal (Quercus infectoria Oliv.) - A Multiaction Drug of Indian Systems of Medicine (INDIA), Phytochemical Evaluation of Chyavanprash (INDIA), Effect of Terminalia catappa Seed Meal-based Diet on the Alkaline and Acid Phosphatase Activities of Some Selected Rat Tissues (NIGERIA), Phytochemical Study of Foeniculum vulgare Mill.- A Mediterranean Medicinal Plant (SPAIN), Traditional Medicinal Plants of Kendrapara District, Orissa, India (INDIA), Evaluation of Diuretic Activity of Six Plants Used for the Treatment of Urinary Diseases in Mexico (MEXICO), The Potential Antibacterial and Antifungal Activities of the Leaves of Mitracarpus scaber Zucc. (Rubiaceae) (BELGIUM, CONGO), Herbal Plant Momordica charantia and its Implications in Diabetes Mellitus (INDIA), Biologicals Effects of Croton lechleri -A Folk Medicinal Plant from South America (BRAZIL), The Active Compounds from Hyperici herba: Traditional versus Modern Knowledge (ROMANIA), Haematological Evaluation of Aqueous Extract of Tithonia diversifolia in Wistar Rats. (NIGERIA), Acanthopanax senticosus Harms Provides Protective Effect in Rat Model of Parkinson\'s Disease (JAPAN), Leaf Anatomical Characters of Stachys byzantina C. Koch, Lamiaceae (BRAZIL), Anti - Mycobacterium tuberculosis Activity of Peruvian Plant Extracts Using a Rapid, Inexpensive Colorimetric Assay (PERU), Antimicrobial Effects of Aqueous and Ethanolic Fractions of Some Local Spices - Ocimum gratissimum and Xylopia aethiopica. (NIGERIA), Comparative Investigations of Antimicrobial Activities and Compositions of Various Aroma Samples - A Short Review (AUSTRIA, BULGARIA, GERMANY), Analgesics and Antipyretic Activities of Ethanolic Extract of Psidium guajava in Rats (NIGERIA), Influence of Sowing Dates on Growth, Seed Yield and Active Substances of Foeniculum vulgare cv. soroksari (IRAN), In vitro Regeneration of Salacia beddomei via Callusing from Cultured Stem Explants (INDIA), Pharmacological Activities of Three Ethnomedicines of Little Andaman (INDIA)